2021
DOI: 10.3390/molecules26216509
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin C Affects Glucose-Stimulated Insulin Secretion in Pancreatic β-Cells and Glucose Uptake in Skeletal Muscle Cells

Abstract: The aim of our study was to investigate the effect of three lignans (schisandrol A, schisandrol B, and schisandrin C) on insulin secretion in rat INS-1 pancreatic β-cells and glucose uptake in mouse C2C12 skeletal muscle cells. Schisandrol A and schisandrin C enhanced insulin secretion in response to high glucose levels with no toxic effects on INS-1 cells. The effect of schisandrin C was superior to that of gliclazide (positive control), a drug commonly used to treat type 2 diabetes (T2D). In addition, wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In addition to the aforementioned pharmacological activities, Sch C was also found to have antiviral activity, [89] and experiments showed that Sch C reduced HBeAg, HBcAg, HBsAg and HBV DNA levels in HBV model mice and increased IFN β production and expression of interferon-stimulated genes (IFIT1, ISG15 and CXCL10). In contrast, a study by D. Lee [90] illustrated that Sch C is also effective in hypoglycemia, enhancing insulin secretion in response to high glucose levels, with no toxic effects on INS-1 cells and better effects than gliclazide (positive control), while enhancing glucose uptake.…”
Section: Othersmentioning
confidence: 95%
“…In addition to the aforementioned pharmacological activities, Sch C was also found to have antiviral activity, [89] and experiments showed that Sch C reduced HBeAg, HBcAg, HBsAg and HBV DNA levels in HBV model mice and increased IFN β production and expression of interferon-stimulated genes (IFIT1, ISG15 and CXCL10). In contrast, a study by D. Lee [90] illustrated that Sch C is also effective in hypoglycemia, enhancing insulin secretion in response to high glucose levels, with no toxic effects on INS-1 cells and better effects than gliclazide (positive control), while enhancing glucose uptake.…”
Section: Othersmentioning
confidence: 95%
“…QKF Improves STZ-Induced Mouse Inflammation. DOP is an inflammatory response caused by high blood glucose [15]. To validate that QKF could reduce the inflammatory expression of STZ-induced mice, we used qRT-PCR and Western blot to determine changes in mRNA and protein levels (Figure 4).…”
Section: Effect Of Qkf On the General Features Of Stz-inducedmentioning
confidence: 99%